Relationship Between Personal Hygiene Behavior Bathing Behavior and Sleeping Behavior with the Incidence of Scabies Among Students at the Manhajul Ulum Islamic Boarding School Ciamis Regency - Adi Nurapandi; Intan Putri Nurlela; Irpan Ali Rahman; Sri Utami Asmarani; Endrian MJW; Panji Wahlanto; Elis Noviati; Lusi Lestari (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2025)
Scabies is a skin disease that is still common in Indonesia and remains a public health problem. According to the World Health Organization (WHO) the incidence of scabies in 2014 was 130 million people worldwide. According to data from the Ministry of Health of the Republic of Indonesia, the prevalence of scabies in 2017 is 6% of the total population of Indonesia, while scabies is still ranked 9 of the 10 largest diseases in West Java Province with a total of 38,854 cases in 2011. Based on outpatient reports of the Rajadesa Health Center the incidence of scabies in months In October 2020 there were around 39 cases, while in the Manhajul Ulum Islamic Boarding School, Ciamis Regency, data was obtained that as many as 60 students suffered from scabies in October 2020. To determine the relationship between personal hygiene behavior, bathing behavior and sleeping behavior with the incidence of scabies among students at the Manhajul Ulum Islamic Boarding School, Ciamis Regency. Quantitative research methods using a correlation design and retrospective research design. Total population of 90 students who suffer from scabies and who do not suffer from scabies in the Manhajul Ulum Islamic Boarding School, Ciamis Regency, and the sampling used the total sampling method, namely the entire population was used as a sample of 90 respondents. The results showed that there were 60 people (66.7%) who suffered from scabies, 34 people (37.8%) who suffered from scabies, 34 people (37.8%) who were in poor category and 36 people (40.0%) suffered from scabies. with the less category. The results of statistical tests showed that there was a relationship between personal hygiene behavior in bathing behavior and the incidence of scabies (p = 0.023 <0.05) and there was a relationship between personal hygiene behavior in sleep behavior and the incidence of scabies (p = 0.011 <0.05) at the Manhajul Ulum Islamic Boarding School. Ciamis Regency. The conclusion of this study states that there is a significant relationship between personal hygiene behavior, bathing behavior and sleep behavior with the incidence of scabies among students at the Manhajul Ulum Islamic Boarding School, Ciamis Regency.